A Map-matching Algorithm to Improve Vehicle Tracking Systems Accuracy - Dewandaru, Agung (2008)

(untitled)
The satellite-based vehicle tracking systems accuracy can be improved by augmenting the positional information using road network data, in a process known as map-matching. Map-matching algorithms attempt to estimate vehicle route and location in a particular road map (or any restricting track such as rails, etc), in spite of the digital map errors and GPS inaccuracies. Point-to-curve map-matching is not fully suitable to the problem since it ignores any historical data and often gives inaccurate, unstable, jumping results. The better curve-to-curve matching approach consider the road connectivity and measure the curve similarity between the track and the possible road path (hypotheses), but mostly does not have any way to manage multiple route hypotheses which have varying degree of similarity over time. The thesis presents a new distance metric for curve-to-curve mapmatching technique, integrated with a framework algorithm which is able to maintain many possible route hypotheses and pick the most likely hypothesis at a time, enabling future corrections if necessary, therefore providing intelligent guesses with considerable accuracy. A simulator is developed as a test bed for the proposed algorithm for various scenarios, including the field experiment using Garmin e-Trex GPS Receiver. The results showed that the proposed algorithm is able to improve the map-matching accuracy as compared to the point-to-curve algorithm. Keywords: map-matching, vehicle tracking systems, Multiple Hypotheses Technique, Global Positioning System.